2021
DOI: 10.3389/fonc.2021.649766
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis and Concurrent Genomic Alterations in Patients With Advanced NSCLC Harboring MET Amplification or MET Exon 14 Skipping Mutation Treated With MET Inhibitor: A Retrospective Study

Abstract: BackgroundMET amplification or METex14 skipping mutations are uncommon oncogenic events in NSCLC patients. Clinicopathological characteristics, concurrent gene alterations, and prognosis of MET TKIs in these patients are yet to be elucidated.MethodsWe retrospectively analyzed the genomic profiles of 43 MET amplifications or 31 METex14 skipping mutations in NSCLC patients with no previous treatment with EGFR TKIs. Survival outcomes were analyzed in evaluable patients receiving MET TKI treatment: MET amplificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“… 3 , 22 Several studies have revealed the beneficial effects of MET inhibitors in patients with MET-driven NSCLC. 23 , 24 , 25 , 26 Nevertheless, the efficacy of MET tyrosine kinase inhibitors (TKIs) in patients with PSC remains poorly described with limited clinical literature available.…”
Section: Introductionmentioning
confidence: 99%
“… 3 , 22 Several studies have revealed the beneficial effects of MET inhibitors in patients with MET-driven NSCLC. 23 , 24 , 25 , 26 Nevertheless, the efficacy of MET tyrosine kinase inhibitors (TKIs) in patients with PSC remains poorly described with limited clinical literature available.…”
Section: Introductionmentioning
confidence: 99%
“…In another retrospective study, MET mutation group also had a better PFS than MET amplified patient group (11.0 months vs 7.0 months). [11]…”
Section: Discussionmentioning
confidence: 99%
“…In another retrospective study, MET mutation group also had a better PFS than MET amplified patient group (11.0 months vs 7.0 months). [11] Among patients with NSCLC harboring MET exon 14 alteration, the patients treated with MET inhibitor had better survival comparing to the patients not treated with targeted therapy, in a retrospective study. [12] In this study, 22 patients had crizotinib in any line.…”
Section: All Patients N (%) Met Alterations Pmentioning
confidence: 99%
“…It is capable of regulating cell proliferation, migration and invasion by activating the downstream MEK–ERK pathway and PI3K pathway 4 . The oncogenic driving variants of MET gene mainly include METex14 skipping and MET amplification 5 . METex14 encodes a structural domain containing the ubiquitin ligase binding site of Y1003 6 .…”
Section: Introductionmentioning
confidence: 99%
“… 4 The oncogenic driving variants of MET gene mainly include METex14 skipping and MET amplification. 5 METex14 encodes a structural domain containing the ubiquitin ligase binding site of Y1003. 6 METex14 skipping is present in about 1%–3% of NSCLC patients and may cause deletion of the binding sites of Y1003 and c‐CBL, abnormal degradation of MET proteins and sustained activation of MET gene.…”
Section: Introductionmentioning
confidence: 99%